แนวทางการนำกีฬาบิลเลียดออกจากบัญชี ข. ตามพระราชบัญญัติการพนัน พุทธศักราช 2478 - นภัสรัญชน์ ไชยวรุตย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Billiards, which has to be practiced, accurate, and needs concentration and in addition, physical ability is also essential in setting a consequence. The reasons that made Billiards legislated as gambling in List B in Gambling Act, B.E. 2478, is the public order and morals. Previously, Billiards was perceived by Thai people as a harmful sport because the teenagers were very addicted to playing Billiards as gambling. It caused their habit to be more interested in gambling which made them unable to focus on working and studying, and also diminished national and economic improvement. However, as the time goes by, the social conditions, concepts and attitudes have changed. Billiards and similar games are lately perceived as sports rather than gambling. Billiards is accepted both in domestic and international, but the law still controls Billiards and similar games that causes an effect on these kinds of sports and also goes against fundamentals and principles of criminal punishment. For these reasons, the freedom of playing Billiards in Thailand is restricted; in contrast, in other countries only prosecutes the one who tries to host Billiards without license as an administrative offense. Therefore, the Gambling Act, B.E. 2478 is not appropriate. This research aims to study the process in repealing Billiards from List B in Gambling Act, B.E. 2478 by researching the cause and effect of Gambling Act, B.E. 2478 to Billiard and similar games in Thailand. Moreover, this thesis also comparatively studies between the offense and law to analyze, compare and suggest the process in repealing Billiards from List B in Gambling Act, B.E. 2478.